Penerapan Customer Experience Design dalam Meningkatkan Loyalitas Pelanggan pada Coffee Shop XYZ di Karawang - Apriyanto, Apriyanto (Jurnal Bisnis dan Manajemen West Science, 2025)
This study investigates the effect of customer experience design on customer loyalty at XYZ Coffee Shop in Karawang. As competition in the coffee shop industry intensifies, creating memorable customer experiences has become essential for ensuring repeat visits and long-term relationships. Using a quantitative approach, data were collected from 175 respondents who had visited XYZ Coffee Shop at least twice. A structured questionnaire with a 5-point Likert scale was employed, and data were analyzed using SPSS version 25. The results show that customer experience design, encompassing ambiance, service quality, employee interaction, digital engagement, and emotional engagement, has a positive and significant effect on customer loyalty. Regression analysis revealed that customer experience explains 58.9% of the variance in loyalty, with emotional engagement and ambiance emerging as the strongest predictors. These findings highlight that enhancing customer experience design is a crucial strategy for building loyalty and sustaining competitiveness in the coffee shop industry.